Busana Kontemporer Terinspirasi dari Bentuk Angsa - Vina Okta Sari; Mirda Aryadi; Nofi Rahmanita3; Fadri Rahmat (INDO PUBLISHING, 2026)
The creation of this work was inspired by the beauty of the swan's form, which possesses distinctive visual characteristics such as a long curved neck, layered feathers, and graceful movements. These characteristics were used as the main source of inspiration in designing contemporary fashion through the application of embroidery techniques as the primary decorative element. The objectives of this project were to design, realize, and present a contemporary fashion collection inspired by the form of a swan. The creation method consisted of three stages: exploration, design, and realization. The exploration stage was conducted through direct observation of swans and literature studies related to the topic. The design stage included trend analysis, moodboard development, alternative sketch creation, and design selection. The realization stage involved the process of garment construction by applying embroidery and beadwork techniques. The materials used included satin bridal fabric, Angso Duo batik fabric, organza, and other supporting materials.The final works consisted of three fashion categories: Ready-to-Wear, Ready-to-Wear Deluxe, and Haute Couture. The characteristics of the swan were represented through embroidered motifs, wing- and feather-inspired garment details, and the use of earth-tone colors such as dark brown, mocha, and cream. The resulting collection combines traditional and modern elements, creating contemporary fashion pieces that are unique, aesthetically appealing, and possess strong artistic value.